Game Edukasi Pembagian Bilangan Berbasis Android Untuk Siswa Kelas 2 Sekolah Dasar - Dyah Triwahyuningtyas; Dela Sari Novaria; Cicilia Ika Rahayu Nita (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The background of this research is the unavailability of fun and non-boring media based on IT. To foster interest and motivation with the concept of playing while learning through an Android-based number division educational game. The research aims at educational games based on Android class II in elementary schools are feasible, practical, and effective. The development method using the 4D model consists of four stages, including the define stage, the design stage, the developing stage, and the dissemination stage. The analysis technique is thorough qualitative and quantitative descriptive data analysis. The results of the study stated that the Android-based number division educational game obtained an average score of 95.83% by experts by stating it was feasible. The Android-based number division educational game was used to get positive responses from teachers and students with an average of 94%. With this android-based number division educational game, student learning outcomes have increased based on the average value reaching 0.47. So that the Android-based number division educational game is practical and effectively applied in the mathematics learning process.Abstrak: Penelitian ini dilatarbelakangi belum tersedianya media menyenangkan serta tidak membosakan berbasis IT. Untuk menumbuhkan minat dan motivasi dengan konsep bermain sambil belajar melalui game edukasi pembagian bilangan berbasis Android. Penelitian bertujuan mengembangkan game edukasi pembagian bilangan berbasis android untuk siswa kelas 2 SD yang layak, praktis dan efektif. Pengembangan menggunakan model 4D yang terdiri dari empat tahap yaitu tahap pendefinisian (define), tahap perancangan (design), tahap pengembangan (develop), dan tahap penyebaran (disseminate). Teknik analisis data menggunakan analisis deskriptif kualitatif dan kuantitatif. Hasil penelitian menyatakan game edukasi pembagian bilangan berbasis android memperoleh skor rata-rata 95,83% oleh para ahli dengan menyatakan layak. Game edukasi pembagian bilangan berbasis android digunakan memperoleh tanggapan positif oleh guru serta peserta didik dengan rata-rata 94%. Melalui game edukasi pembagian bilangan berbasis android tersebut, hasil belajar peserta didik menjadi meningkat nilai rata-rata mencapai 0,47. Sehingga game edukasi pembagian bilangan berbasis android praktis dan efektif diterapkan dalam proses belajar matematika